2015
DOI: 10.5489/cuaj.2793
|View full text |Cite
|
Sign up to set email alerts
|

Few modifiable factors predict readmission following radical cystectomy

Abstract: Introduction: We sought to determine the patient and providerrelated factors associated with readmission after radical cystectomy (RC) for bladder cancer. In this era of healthcare reform, hospital performance measures, such as readmission, are beginning to affect provider reimbursement. Given its high readmission rate, RC could be a target for quality improvement. Methods: We reviewed bladder cancer patients who underwent RC in California's State Inpatient Database (2005Database ( -2009) of the Healthcare Cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
1
10
1
Order By: Relevance
“…However, prior work suggests that targetable and mutable factors driving readmission after RC are elusive. It may be the case that very early readmissions are largely unmodifiable, consistent with existing findings across the full 30-day readmission time frame [12,13].…”
Section: Introductionsupporting
confidence: 83%
“…However, prior work suggests that targetable and mutable factors driving readmission after RC are elusive. It may be the case that very early readmissions are largely unmodifiable, consistent with existing findings across the full 30-day readmission time frame [12,13].…”
Section: Introductionsupporting
confidence: 83%
“…Recent studies have emphasized the importance of post-acute care after surgery 11 , 19 27 , which we found may prevent short-term readmission. Our findings contradict previous studies showing an elevated risk of readmission in patients discharged to poste-acute care facilities after surgery 22 , 23 , 26 , 27 . These studies evaluated discharge to any post-acute care facility, without accounting for whether they were institutional or rehabilitative placements.…”
Section: Discussioncontrasting
confidence: 98%
“…On one hand, it has been suggested that maintenance of care after surgery might reduce risk of readmission 19 , 24 , 25 . On the other hand, discharge to a post-acute care facility was an independent predictor of readmission after surgery 22 , 23 , 26 , 27 . Inpatient rehabilitation constitutes one of the only active interventions, as opposed to simply providing prolonged institutional care.…”
Section: Introductionmentioning
confidence: 96%
“…For example, variables expected to be associated with readmission such as age, sex, comorbidities and higher ASA scores are not consistently associated with readmissions. 6,9,10,12,25 Patient characteristics remain poor targets for modification in decreasing readmissions due to the fact they usually only explain a small fraction of deviation in final outcomes, and their risk factors (e.g. age, sex) are often not amenable to modifications.…”
Section: Current Readmission Rates and Associated Risk Factors For Mamentioning
confidence: 99%
“…Interestingly, those discharged to a skilled nursing facility or a rehabilitation facility (SNF) are more likely to have readmissions than those with other discharge destinations (home or home, with home health). 6,7 This is an interesting phenomenon and could stem from a few possible reasons: (1) patients going to SNF are sicker or had more complications during their index hospitalization and thus require more readmissions for underlying medical and surgical issues; (2) SNFs are not equipped with the understanding of complex surgeries (e.g. urinary diversions) their patients have undergone, leading to readmissions; or (3) the reliance on SNFs leads to a premature transference of care from the inpatient side before our patients are actually ready for discharge form acute hospital care.…”
Section: Introductionmentioning
confidence: 99%